Game Design, Gender and Personalities in Programming Education - Theodoropoulos, Anastasios; Lepouras, George (Frontiers in Computer Science, 2022)
In a changing world programming learning is becoming more and more essential in education. And, there are many programming environments and teaching approaches that address the learning needs of students in CS education. A single programming tool or a method do not fit all students. Research has focused on gender differences and there is high interest in increasing female participation. Games and especially game-design tend to impact perceived usefulness of programming environments. Moreover, personality traits like cognitive style and emotional intelligence (EQ) seem to correlate with technology and achievement in programming. In this study, the effects of three different programming environments were investigated, in high school settings, by creating games and taking into account gender and personality characteristics. Three groups were formed, group A created games with Scratch, group B used App Inventor and made games for mobile devices, while group C created interactive stories-games with Alice 3D. This study was seeking to find possible biases based on gender, learning perception, usage and students' personalities between the three experimental conditions. One hundred and sixty three students aged 14–15 years old participated in the study, and data were collected through pre activity and post activity questionnaires. Results show different gender preferences for the three programming tools and, in some cases, different personalities (cognitive styles and EQ) have different learning preferences. Moreover, all programming environments had different emotional effects on the students. The study concludes with guidelines for programming learning environments that respect individual learning preferences and aim to maximize learning effectiveness.